2017
DOI: 10.3390/en10122109
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Design of a Multi-Carrier Microgrid (MCMG) Considering Net Zero Emission

Abstract: Abstract:In this paper, a two-stage optimum planning and design method for a multi-carrier microgrid (MCMG) is presented in the targeted operation period considering energy purchasing and the component's maintenance costs. An MCMG is most likely owned by a community or small group of public and private sectors comprising loads and distributed energy resources (DERs) with the ability of self-supply to regulate the flows of various energies to local consumers. The operation cost is undoubtedly reduced by selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 37 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…Zheng et al [41] go further and develop a load shifting algorithm based on the state of renewable energy generation and TOU tariff using linear programming, while optimally designing a biomassintegrated micro-grid. Similarly, Amir et al [42] have reported on a two-stage method for optimal planning and scheduling of a multi-carrier micro-grid under the TOU pricing scheme. Hakimi and Moghaddas-Tafreshi have optimally sized a smart micro-grid that incorporates domestic flexible loads.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zheng et al [41] go further and develop a load shifting algorithm based on the state of renewable energy generation and TOU tariff using linear programming, while optimally designing a biomassintegrated micro-grid. Similarly, Amir et al [42] have reported on a two-stage method for optimal planning and scheduling of a multi-carrier micro-grid under the TOU pricing scheme. Hakimi and Moghaddas-Tafreshi have optimally sized a smart micro-grid that incorporates domestic flexible loads.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The investment cost of selected components (CHP, transformer, steam boiler, and PV) are modeled in Equation (16). The NPV of energy purchase cost and sales revenue from the utility grid on the planning horizon is formulated in the first and second term of Equation (17), respectively.…”
Section: Objective Function and Constraintsmentioning
confidence: 99%
“…A methodology to identify the optimal size and efficiency of a combined heat and power (CHP) plant is presented . Amir et al propose a long‐term MCMG expansion planning model in the electricity, natural gas, and district heat grid‐connected mode by implementing the net zero emission constraints over the planning horizon. The objective is to evaluate and minimize the total net present value of investment, operation, and maintenance costs, while the net zero emission constraint is satisfied.…”
Section: Introductionmentioning
confidence: 99%
“…The MILP method presents some scalability limits as soon as binary variables are introduced to approximate non-convex constraints rather than non-linear programing. Reference (Amir et al , 2017a) proposes a long-term multi-carrier microgrid expansion planning model in the electricity, natural gas and district heat grid-connected mode by considering the net zero-emission constraints over the planning horizon. The objective is to evaluate and minimize the total net present value cost, including investment, operation and maintenance, while the net zero-emission constraint is satisfied.…”
Section: Introductionmentioning
confidence: 99%